2010
DOI: 10.1002/glia.20965
|View full text |Cite
|
Sign up to set email alerts
|

mGLU3 metabotropic glutamate receptors modulate the differentiation of SVZ‐derived neural stem cells towards the astrocytic lineage

Abstract: Neural stem cells (NSCs) isolated from the subventricular zone (SVZ) of postnatal mice, and cultured as neurospheres, expressed functional mGlu3 receptors. Following mitogen withdrawal and plating onto poly-ornitine-coated dishes, cells dissociated from the neurospheres differentiated into GFAP(+) astrocytes (about 85%), and a small percentage of beta-III tubulin(+)-neurons and O1(+)-oligodendrocytes. Activation of mGlu3 receptors with LY379268 (100 nM, applied every other day), during the differentiation peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 60 publications
(41 reference statements)
1
19
1
Order By: Relevance
“…We are aware of the interpretative limitations of data generated by single mGlu ligands, as the distinct functions of mGlu2 and mGlu3 are not fully understood. For this reason, even if we did not observe significant effects of ALC on mGlu3 protein levels, at present we cannot exclude that this receptor subtype, which has been shown to be functionally expressed by adult NPC (Di Giorgi-Gerevini et al, 2005;Ciceroni et al, 2010), may also be involved. We also proved that chronic ALC reverted depressive-like behavior in a predictive animal model.…”
Section: Discussionmentioning
confidence: 56%
“…We are aware of the interpretative limitations of data generated by single mGlu ligands, as the distinct functions of mGlu2 and mGlu3 are not fully understood. For this reason, even if we did not observe significant effects of ALC on mGlu3 protein levels, at present we cannot exclude that this receptor subtype, which has been shown to be functionally expressed by adult NPC (Di Giorgi-Gerevini et al, 2005;Ciceroni et al, 2010), may also be involved. We also proved that chronic ALC reverted depressive-like behavior in a predictive animal model.…”
Section: Discussionmentioning
confidence: 56%
“…This mechanism cannot be applied here because we have eliminated the endogenous excitotoxic component from A␤ neurotoxicity with a cocktail of ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid/N-methyl-D-aspartate re- ceptor antagonists (see above). In cultured neural stem cells, mGlu3 receptors negatively regulate the activity of bone morphogenetic protein receptors, which share the same transduction mechanisms of TGF-␤ receptors (Ciceroni et al, 2010). It will be interesting to examine whether neuronal mGlu2 receptors functionally interact with receptors that support neuronal survival, such as TGF-␤ receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological activation of mGlu3 receptors inhibits the astrocytic differentiation of neural stem cells isolated from the SVZ by negatively modulating BMP receptor signaling (Ciceroni et al, 2010). We also demonstrated that mGlu2/3 receptor activation by neurons induces TGF-β1 secretion, leading to GFAP gene activation and astrocyte differentiation (Romão et al, 2008).…”
Section: Role Of Neuronal-derived Molecules In Astrocyte Differentiatmentioning
confidence: 93%